Art Inheritance : Revitalizing Traditional Material Culture Motifs through Innovative Graphic Design and Artistic Expression - Marzie, Hatef Jalil; Qistina Donna, Lee Abdullah; Natasha, Rusdy Wong; Loh, Ngiik Hoon; Mazdan, Ali Amaran (University of Novi Sad, 2023)
Orang Ulu's culture and traditions are adapting to modernization and finding new ways to thrive amidst changes that have influenced various aspects of their lives and material culture in Malaysia. This paper highlights the exciting potential for Orang Ulu’s material culture to flourish through the development of motif design and presents the first Orang Ulu woven fabric in a 3D graphical view. Motif design is a beautiful way to preserve and promote the rich cultural identity of Orang Ulu through graphical expression. It also has the potential to boost the local economy by providing employment opportunities for skilled artisans. The paper highlights the importance of Orang Ulu motif design in their material culture, emphasizes the value of art as a tool for cultural expression and preservation, and outlines the development of these designs through graphic design and research. This study has adopted mixed-methods research to achieve its goal. The accomplished method for this study is categorized into three phases: research and inspiration in Orang Ulu's material culture market; 2D motif design conceptualization; and 3D artistic creation. This study recommends exploring the potential for incorporating Orang Ulu motifs in apparel products. The findings showcase the exciting potential for small and medium enterprises to preserve and promote the Orang Ulu cultural heritage and sustainability while providing economic benefits for the community.